Economic calibrated models for water allocation in agricultural production: A review. (July 2016) - Graveline, N.
Abstract: There is a growing need to assess the effects of policies and global changes on both water resources and agriculture. Agricultural programming models are adequate to study this topic as their functional forms and calibration capacities make them suitable to represent real agricultural production systems and explicit the link between water and production. We present a review of the research on agricultural economic programming models that represent water demand and allocation among farming activities for different problem settings. The different types of models are discussed and particularly the integration of water into the production function so as to reflect the agronomic response of yields to varying levels of water. Uncertainty and risk integration as well as spatial and temporal scale issues are reviewed as they are determining to model results in a science support to policy perspective. A research agenda for future research in this field is provided. Highlights: We review the literature on economic water programming models. They enable to assess impacts of policies and changes in constraints or costs. Flexibility in their set up makes them operational tools to support policy making.